An Analytical Study of Sir Syed Ahmad Khan Number of “Saheefa”: صحیفہ " کا سر سید احمد خاں نمبر ۔۔۔۔ تجزیاتی مطالعہ" (DARYAFT, 2023)
“Saheefa” is renowned research journal of Pakistan. Scholars need to consult its contents for seek of knowledge, literary taste and to flourish their researches, and a reader can get a pleasant food of knowledge as well. Since 1956, the year of its beginning, “Saheefa” get and has been maintaining a graceful status of a research journal. It has been publishing valuable research works during his 65 years life.  “Saheefa” is also in practice of publishing its special numbers on special events and personalities accordingly, presenting their works and services appraise worthy. Majlis Traqi e Adab has published a special issue of “Saheefa” on 200th Birthday of Sir Syed Ahmad Khan. In this special issue, a number of articles of this special issue are included regarding great works and services of Sir Syed Ahmad Khan for Islam and betterment of Muslims of Subcontinent.  All writers of the articles threw the light in their writings on different aspects through various angles on great works and services of Sir Syed Ahmad Khan. The writer of this article highlighted the key features of mentioned articles in detail. She discusses the importance of each article in view of the life and achievements of Sir Syed Ahmad Khan towards Urdu Literature, politics of India and social issues of the Muslims of the Sub-Continent
Keywords: Special, Issue, Flourish, Personality, Literature, Services, Subcontinent, Angles